Prevalence of Dunning Kruger effect in first year medical students in a tertiary care hospital - Deb, Novonil; Roy, Poulami (International Journal Of Community Medicine And Public Health, 2021)
Background: Dunning Kruger (DK) effect refers to overestimation of one’s ability which is attributed to their inadequacy of metacognitive skills i.e., the low-performing individuals are often nescient of their incompetence which leads them to reach fallacious conclusions and make regrettable choices. Objectives of the study were to assess the degree of DK effect among the first-year medical students and to compare the associated socio-economic variables. Methods: A descriptive cross-sectional study was conducted among the interested first-year medical students of North Bengal medical college and hospital from March 2021 to April 2021 using a questionnaire. Responses were recorded in Microsoft excel 2017, analysed, and presented in form of tables and charts following principles of descriptive statistics. Results: The overall prevalence of DK effect was found to be 78.38% among the first-year medical students. Higher prevalence was observed among females (80.28%) as compared to males (75%). Students having low study hours (79.13%), no academic achievements (77.5%), and greater hours of sleep (79.74%) manifested more predisposition to DK effect. Conclusions: In our research, we have noticed a higher DK effect among the first-year medical students, which might hamper the quality of treatment and patient care in the future. Proper orientation and counselling methods are required to overcome this phenomenon.